Negative Impact of Vitamin D Deficiency at Diagnosis on Breast Cancer Survival: A Prospective Cohort Study - Almeida-Filho, Benedito Souza [UNESP]; Omodei, Michelle Sako [UNESP]; Buttros, Daniel A. B. [UNESP]; Carvalho-Pessoa, Eduardo [UNESP]; Carvalho-Pessoa, Carla Priscila [UNESP]; De Luca Vespoli, Heloisa [UNESP]; Nahas, Eliana Aguiar Petri [UNESP] (Hindawi, 2022)
Objective. We prospectively evaluated the association between vitamin D concentration at diagnosis and overall survival (OS), disease-free survival (DFS), and cancer-specific survival (CSS) in postmenopausal women treated for breast cancer. Methods. This study included 192 patients newly diagnosed with invasive breast cancer, aged ≥45 years, and serum 25-hydroxy vitamin D (25 (OH)D) concentration assessment at diagnosis. Patients were classified into groups according to 25 (OH)D concentrations: sufficient (≥30 ng/mL), insufficient (between 20 and 29 ng/mL), and deficient (<20 ng/mL). The primary outcome was OS, and the secondary outcomes were DFS and CSS. The Kaplan-Meier curve and Cox regression model were used to assess the association between 25 (OH)D concentrations and survival rates. Differences in survival were evaluated by hazard ratios (HRs). Results. The mean age was 61.3 ± 9.6 years, 25 (OH)D concentration was 26.9 ± 7.5 ng/mL (range 12.0-59.2 ng/mL), and the follow-up period was between 54 and 78 months. Sufficient 25 (OH)D was detected in 33.9% of patients, insufficient in 47.9%, and deficient in 18.2%. A total of 51 patients (26.6%) died during the study period, with a mean OS time of 54.4 ± 20.2 months (range 9-78 months). Patients with 25 (OH)D deficiency and insufficiency at diagnosis had a significantly lower OS, DFS, and CSS compared with patients with sufficient values (p<0.001). After adjustment for clinical and tumoral prognostic factors, patients with 25 (OH)D concentrations considered deficient at diagnosis had a significantly higher risk of global death (HR, 4.65; 95% CI, 1.65-13.12), higher risk of disease recurrence (HR, 6.87; 95% CI, 2.35-21.18), and higher risk of death from the disease (HR, 5.91; 95% CI, 1.98-17.60) than the group with sufficient 25(OH)D concentrations. Conclusion. In postmenopausal women treated for breast cancer, vitamin D deficiency and insufficiency at diagnosis were independently associated with lower OS, DFS, and CSS compared with patients with sufficient 25(OH)D concentrations.